Target validation in drug discovery - Metcalf, Brian W.; Dillon, Susan, 1952- (Academic Press, 2007)
This work presents a comprehensive contemporary framework for approaching target validation in drug discovery. It begins with a detailed description of new enabling technologies, including aptamers, RNA interference, functional genomics, and proteomics. The next section looks at biologic drug development with in-depth discussion of lessons learned from such well-known cases as Erbitux, Herceptin, and Avastin. Additional targets known as "second generation" drugs, which can be identified when disease pathways are validated by biologics, present new possible small molecule therapeutics and serve as the focus of the final section of the book